OPTIMASI PRIMER SINGLE NUCLEOTIDE AMPLIFIED POLYMORPHYSM (SNAP) PADA GEN BRASSINOSTEROID (BRI) KELAPA SAWIT - Roberdi Roberdi; Ogi Ajitiyo Ramadhan (Universitas Nusa Bangsa, 2019)
Optimisation of Single Nucleotide Amplified Polymorphism (SNAP) Primers in Brassinosteroid (BRI) Gene of Oil PalmÂ Oil palm varieties that have high yields still have a high rate of stem height increase, and it has an impact on difficulties at harvest. Brassinosteroid (BRI) is one of the growth hormones that regulate stem height increase. In this study, the sample used is three types of oil palm, namely E. guineensis which represents the height growth of normal oil palm stems, E. oleifera which represents slow stem height growth, and the result of crossing or hybrid Eo x Eg which is expected to inherit the traits between the two the crossed parent. Sequencing was carried out on samples using a specific primer for the BRI gene that triggers elongation and division of stem cells. The Single Nucleotide Amplified Polymorphisms (SNAP) primers used in the analysis process need to find the optimum temperature to obtain the optimum PCR conditions. Four primers of Single Nucleotide Amplified Polymorphism (SNAP) that get the optimum temperature with a mixture of normal reagents are BRI 69 Alt-Rev and BRI 562 Ref-Rev at 55oC, BRI 1206 Alt-Rev at 57oC and BRI 1206 Ref-Rev at 58oC. Two primers require additional MgCl2 in the reactant mixture, namely BRI 69 Ref-Rev at 55oC and BRI 2115 Alt-Rev at 56oC.Keywords: Oil palm, Brassinosteroid, Primer, DNA, GenesABSTRAKÂ Varietas-varietas kelapa sawit yang memiliki daya hasil tinggi umumnya masih memiliki laju pertambahan tinggi yang relatif cepat dan berakibat pada kesulitan saat panen. Brassinosteroid (BRI) merupakan salah satu hormon pertumbuhan yang mengatur pertambahan tinggi batang. Pada studi ini, Sampel yang digunakan adalah tiga jenis kelapa sawit yaitu sampel E. guineensis yang mewakili pertumbuhan tinggi batang kelapa sawit normal, E. oleiferaÂ yang mewakili pertumbuhan tinggi batang lambat, dan hasil persilangan atau hibrida Eo x Eg yang diharapkan mewarisi sifat antara kedua induk yang disilangkan. Sekuensing dilakukan pada sampel menggunakan primer spesifik gen BRI yang memicu pemanjangan dan pembelahan sel batang. Primer Single Nucleotide Amplified Polymorphisms (SNAP) yang digunakan dalam proses analisis perlu dicari suhu optimumnya agar didapatkan kondisi PCR yang optimum sehingga dihasilkan produk PCR yang spesifik. Empat primer Single Nucleotide Amplified Polymorphism (SNAP) yang mendapatkan suhu optimum dengan campuran pereaksi normal yaitu BRI 69 Alt-Rev dan BRI 562 Ref-Rev pada suhu 55oC, BRI 1206 Alt-Rev pada suhu 57oC dan BRI 1206 Ref-Rev pada suhu 58oC. Dua primer membutuhkan tambahan MgCl2 pada campuran pereaksinya yaitu BRI 69 Ref-Rev pada suhu 55oC dan BRI 2115 Alt-Rev pada suhu 56oC.Kata Kunci: Kelapa sawit, Brassinosteroid, Primer, DNA, Gen